Ofício das Paneleiras de Goiabeiras (Vitória-ES) : práticas de uma atividade artesã entre os interstícios da(s) memória(s) e práticas coletivas, dispositivos patrimoniais e ecossistemas - Silva, Adimilson Renato da (Universidade do Vale do Rio dos Sinos, 2019)
This thesis deals with the possibility of intelligibility of the cultural narrative of the paneleiras and their partners interchanged between the places of management of Ofício das Paneleiras de Goiabeiras. This form of institutional know-how traditional clay pot was institutionalized as an office when identified, registered and granted as the first cultural good of an intangible nature registered in the Book Saberes do Iphan. From the perspective of the engagement of the craftsman and artisan actors in the paneleira activity, these women and men realize the making and the commercialization of clay pots. In this movement it deals with clay, the headquarters of the association and in the, in contact with the mangrove and the neighborhood of Goiabeiras (Vitória-ES), the paneleiras are immersed in the tensions and assimilations of identity constructions by which they recreate family relations, of kinship and neighborhood. With the intention of researching the opening of this collective of craftsmen and artisans in front of their institutional, community, individual and collective partnerships the following question was asked: What are the places for the management of Ofício das Paneleiras de Goiabeiras and their interactions along the culture-environment relationship to make intelligible the know-how of the paneleiras and their partners, involved and articulated in the production, circulation and commercialization of black clay pots? To situate this study from the theoretical point of view, we go through considerations about three structuring axes of the research framework intended for this research: Cultural narrative and its patrimonial dimensions; Perception of the "being-in-the-world" between the "world of consumer goods"; Communities of practices and places of management of self and of the collectivity. From the methodological point of view, we persist in the elaboration of ethnographies of the senses and latent, emerging and manifest values from the logics of exchange of the places of management of Ofício das Paneleiras. This demanded to delimit the areas of approach, problematization and assimilation and / or resistance of the "reservations" and "principles of meaning", re-signifying or making durable the value regimes envisaged in artifacts (crafts), in the conducts and in the environment of the paneleira activity. The notion of environmental context understood as the scope of creativity and interpellation of life diversifies the records of obligations and margins of action existing in the traditional community located in Goiabeiras Velha. Legitimate participation in this instance of clay pot know-how is observed while senses and values are tangled in the time of "maturation" of generative skills at the stage of development. To this end, even though it is a seemingly conflictive discussion to treat peasants as a "collectivity", we recognize this dimension of the artisan collective as a potential that interacts and suffers relations of human and nonhuman actors. The approach of the comprehensive epistemology pursued in this work made it possible to problematize the possibilities and limits of the logics of ambivalent exchange for the contraction or amplitude of the intelligibility of the cultural narrative understood as Ofício das Paneleiras de Goiabeiras.
Keywords: Paneleiras de Goiabeiras; Patrimônio cultural; Lugares de gestão; Lógicas de permuta; Paneleiras de Goiabeiras; Cultural heritage; Places of management; Permutation logical; ACCNPQ::Ciências Humanas::Sociologia